Original paperPhotodynamic diagnosis of skin cancers – own experiences - Rykała, Jan; Peszyński-Drews, Cezary; Witmanowski, Henryk; Kruk-Jeromin, Julia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Introduction: Photodynamic diagnosis of tumours is a new procedure utilizing the combined action of light and a photosensitizing drug. The laser-fibre optic delivery system allows the visualisation of superficial and deep localized neoplasms including malignancies of the skin, oesophagus, endobronchial tract, stomach, urinary bladder, female genital tract, and other sites. The putative action mechanism depends on evocation of fluorescence of a photosensitizing drug within cancer tissue (important for non-invasive optical diagnosis). Material and methods: Diagnostic investigations of cutaneous changes with the photodynamic method using 5% aminolevulinic acid and monochromatic light emitted by a Stortz lamp were performed in the Diagnostics and Laser Therapy Centre, Technical University of Łódź, from 2001 to 2007. Results: Topical ALA diagnosis has the following advantages: it is non-invasive, it is well tolerated by patients, it can be used to diagnose multiple superficial lesions, and it shows the border of the lesions well. Conclusions: The method of photodynamic diagnostics does not replace the necessity of performing histopathological examinations, which still are of basic importance, but the places of affected skin specimen sampling may be determined by a non-invasive method. Moreover, the method of so-called “optic biopsy”, supplementing diagnostic investigations by determining the precise boundary line of the change, enables first of all total tumour excision, obtaining simultaneously an optimal cosmetic effect, particularly in the case of superficial changes.